FORMULASI DAN EVALUASI FISIK SEDIAAN GEL EKSTRAK SIRIH CINA (Peperomia pellucida L. Kunth) DENGAN VARIASI CARBOPOL SEBAGAI GELLING AGENT - Putri, Vania Santika; Sugiyanti, Sugiyanti; Dewi, Aptika Oktaviana Trisna (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The Chinese betel plant is a herbaceous plant belonging to the Piperaceae family. The Chinese betel plant (Peperomia pellucida L. Kunth) contains alkaloids, flavonoids, saponins and tannins which help the wound healing process. This study aims to determine the physical quality of Chinese betel gel preparations and the effect of variations in carbopol concentrations as a gelling agent on the physical properties of Chinese betel extract gel. Chinese betel leaf extraction was carried out by maceration method using 96% ethanol as solvent. Gels were made into three formulas with variations in carbopol concentrations, namely F1 (0,5%), F2 (1%), and F3 (2%). The gel preparations were then subjected to physical tests including organoleptic tests, homogeneity, pH, adhesion, spreadability, and viscosity. The homogeneity and organoleptic test results for the three gel formulas were homogeneous, had a blackgreen color, semi-solid form, and had a characteristic odor of the extract. The three gel formulas had a pH of 4,93-5,48, adhesion between 1,13-2,14 seconds, and spreadability ranging from 5,04-6,09 cm. The results of the viscosity test for the three formulas were in the range of 3.913,33-3.915 cPss. Based on the SPSS test results, variations in carbopol concentrations had no significant effect on adhesion, gel spreadability, pH and gel viscosity.